Upaya Meningkatkan Pemahaman Bahaya Bullying Melalui Bimbingan Klasikal bagi Siswa SMPN 22 Mataram - Ni Ketut Seriasih (Jurnal Paedagogy, 2021)
This study aims to describe the increased understanding of the dangers of bullying through classical guidance to class VIII.A students of SMPN 22 Mataram in the 2020/2021 academic year. This research is a classroom action research. The subjects in this study were 32 students. The instrument used in this research is a questionnaire. While the data analysis technique to test the difference in the mean of the pretest and posttest after the action was carried out was using the t-test. The results showed that after being given classical guidance services, the understanding of the dangers of bullying was in the very high category with a total frequency of 23 which was 71, 875%. In the very high category it has reached more than half the number of students. In the high category with a total frequency of 6 of 18, 75 %, in the medium category the number of frequency 3 of 9, 375%, in the low category the number of 0 is 0%, the category is very low with a total frequency of 0 of 0%. Thus, it can be concluded that classical guidance is an effective and innovative strategy to increase the understanding of class VIIIA students of SMPN 22 Mataram regarding the understanding of the dangers of bullying.